Post‐endoscopic retrograde cholangiopancreatography pneumothorax: Report of two cases and literature review - Jha, Ashish Kumar (JGH Open, 2018)
Pneumothorax is a very rare complication of endoscopic retrograde cholangiopancreatography. Here, we report two cases of pneumothorax following ERCP and sphincterotomy for choledocholithiasis. Patient was treated successfully with laprotomy and repair of a rent in the posterolateral wall of the second portion of duodenum. We also review the literature. [Image: see text]